2002
DOI: 10.1176/appi.ps.53.9.1173
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Missed First Appointments at a Psychiatric Clinic

Abstract: This study identified characteristics ofpatients who missed their intake appointments at a university psychiatric outpatient clinic for persons with serious mental illness after referral from a state agency. Of the 313 patients whose charts were reviewed, 113 (36 percent) missed their appointment. Demographic characteristics, DSM-IV diagnoses, clinician rating scales, and psychopharmacological therapy were compared between attenders and nonattenders. Five predictors of nonattendance were significant: being you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
2
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(78 citation statements)
references
References 10 publications
10
63
2
3
Order By: Relevance
“…In a comprehensive study of 221 000 primary care appointments in Sheffield, there was a strong correlation (r = 0.72) between non-attendance and the Townsend Deprivation Index Score for the patient's medical practice (Waller & Hodgkin, 2000). Kruse et al (2002) examined the medical records of 313 individuals with serious mental illness who were attending a US psychiatric out-patients clinic and found that 36% had missed their first appointment. The significant predictors were young age, Hispanic ethnicity, having a poor family support system, not having health insurance and also poor adherence to psychotropic medication (Kruse et al, 2002).…”
Section: Environmental and Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a comprehensive study of 221 000 primary care appointments in Sheffield, there was a strong correlation (r = 0.72) between non-attendance and the Townsend Deprivation Index Score for the patient's medical practice (Waller & Hodgkin, 2000). Kruse et al (2002) examined the medical records of 313 individuals with serious mental illness who were attending a US psychiatric out-patients clinic and found that 36% had missed their first appointment. The significant predictors were young age, Hispanic ethnicity, having a poor family support system, not having health insurance and also poor adherence to psychotropic medication (Kruse et al, 2002).…”
Section: Environmental and Demographic Factorsmentioning
confidence: 99%
“…Kruse et al (2002) examined the medical records of 313 individuals with serious mental illness who were attending a US psychiatric out-patients clinic and found that 36% had missed their first appointment. The significant predictors were young age, Hispanic ethnicity, having a poor family support system, not having health insurance and also poor adherence to psychotropic medication (Kruse et al, 2002). In a study of 600 patients followed up after an emergency psychiatric assessment, Dobscha et al (1999) found that homeless people were the least likely to attend, managing only a 34% follow-up rate.…”
Section: Environmental and Demographic Factorsmentioning
confidence: 99%
“…Several studies have shown that taking prescribed psychotropic medications is significantly associated with higher attendance of psychiatric appointments (Kruse, Rohland, & Wu, 2002;Mitchell & Selmes, 2007b). This suggests that patients in combined therapy may be more likely to attend psychotherapy sessions if they adhere to their prescribed medication regimen.…”
Section: Treatment Typementioning
confidence: 99%
“…Similarly, they showed that unemployment and homelessness are associated with poor treatment adherence. Additionally, other studies have shown that younger patients, those in lower socio-economic status (SES) categories and racial/ethnic minorities (particularly Hispanic) are more likely to drop out of treatment (Kruse, Rohland, & Wu, 2002;Mitchell & Selmes, 2007b). Unfortunately, racial/ethnic minorities commonly belong to lower SES categories in the United States, and lower income may reduce family and social support available.…”
Section: Support For Patientsmentioning
confidence: 99%
“…We anticipated the policy could result in treatment disruptions among all patients with bipolar illness that may reflect differences in treatment effectiveness, administrative problems (confusion about the policy, the hassle of seeking preauthorization) or other factors (5)(6)(7)(8). We also anticipated that disruptions in pharmacotherapy after policy implementation could be associated with either increased use of non-drug health services due to increased symptoms or dropping out of the healthcare system that may reflect differences in patient compliance and care-seeking behavior as prior-authorization adds another barrier to care for a very vulnerable patient population; previous research has reported an association between medication nonadherence and reduced frequency of physician visits (19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%